Penerapan Pelatihan Edulead Oleh Manajemen Sekolah dan Dampaknya Pada Stake Holder Sekolah - Alfikalia, Alfikalia (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2021)
The purpose of this research was to gain preliminary insights on how the participants of Edulead Training implemented the training in their respective institutions and the impacts perceived after the implementation. Research method used to measure the implementation was survey method using online questionnaire, with open and closed questions. The data analise were from 25 out of 28 training participants participated in the data collection. The results showed that all respondents reported that they had implement the training on their job. There were three channels reported on how the training materials being implemented: by conducting training to teachers and other members of school management, applying the materials themselves, and conducting socailization/knowledge sharing to teachers, other members of school management, and parents. After implementing training materials on their respective institutions, all participants reported positive impact. The positive impact reported was seen in teachers, students, other members of school management, working environment, and parent